Tomato cell cultures as innovative plant biostimulants: evaluation of its effect on pepper seeds germinated under salinity conditions - Martí-Guillén, José Manuel; Martínez-Lorente, Sara Esperanza; Miras-Moreno, Begoña; Pedreño, María Ángeles; Almagro, Lorena; Sabater-Jara, Ana Belén (Frontiers in Plant Science, 2025)
The edaphoclimatic pressure derived from climate change is challenging modern agriculture by decreasing the yield of crops necessary to feed the increasingly growing world population. In response to these constraints, plant biostimulants have emerged as a promising and environmentally sustainable approach to enhance crop yield and performance under these adverse conditions. Among the different types of biostimulants, higher plant-derived biostimulants (hPDBs) stand out due to their favorable attributes, including low production costs, safety and being environmentally friendly. Furthermore, their rich composition in diverse bioactive compounds positions them as valuable tools for improving plant growth and stress tolerance within sustainable agricultural systems. In this work, tomato cell cultures elicited with 25 mM Me-β-cyclodextrins and 100 µM methyljasmonate were used to produce a novel type of hPDB through biotechnological tools: tomato biostimulant (TB). Comprehensive untargeted metabolomic analysis revealed a distinctive metabolic profile of TB compared to unelicited cell cultures. Among the discriminant metabolites that explain the differences between the chemical profiles, several were fatty acids, as well as phenolic compounds, including flavonoids and other specialized plant metabolites. TB was applied as seed priming in pepper seeds, with the goal of enhancing the germination process under salt stress and obtaining seedlings with improved vigor and physiological quality and less oxidative damage. The results showed an improvement in germination parameters, such as MGT (-10%), GI (+25%) and VI (+47%); and in oxidative stress markers, by decreasing H2O2 content by -24%, and promoting POX activity by +35%, compared to non-primed seeds subjected to salt stress. Thus, TB constitutes a novel biostimulant with potential to alleviate salt stress in pepper seeds by promoting antioxidant defenses and reducing oxidative damage.